Pengaruh Manajemen Aset Terhadap Tingkat Optimalitas Aset Tetap (Tanah dan Bangunan) Pemerintah Kabupaten Sorong - Jusmin, Nursalim (Universitas PGRI Madiun, 2018)
This research aims to analyze the impact of asset management towards optimality offixed assets (land and buildings) in the Local Government in Kabupaten Sorong. By usingpurposive sampling method the number of research samples was takenas much as 48respondents. The variables used are assets inventory, audit legal of assets assessment, aswell as supervision and asset control. Based on the analysis result using Multiple LinearRegression test indicated that the asset inventory individually are proven have positive andsignificant influence toward optimality of fixed assets (land and buildings) that meansconsistent with the hypothesis, individually the legal audit of assets are not proved havepositive and significant influence to optimization of fixed assets (land and buildings) thatmeans not consistent with the hypothesis, an individual assessment of the assets areindicated are proved has positive influence to optimality of fixed assets (land and buildings)that means consistent with the hypothesis, the supervision and asset control is proved havepositive and significant influence to optimization of fixed assets (land and buildings) thatmeans consistent with the hypothesis. While the analysis results together /simultaneouslyindicated that all four variables, namely the asset inventory, audit legal of assets, assetsassessment as well as supervision and assets control are proved to have significant andpositive influence to optimality of fixed assets (land and buildings) this is proved by the valueof F count > F-table.